High-strength asphalt composite material and preparation method thereof

By adding waste rubber powder, reinforced filler and modified polyimide fiber to the asphalt composite material, the synergistic effect of nanocellulose and zinc oxide is used to solve the problem of aging asphalt material, and the aging resistance of asphalt pavement is improved. Durability extends service life.

CN119264687AInactive Publication Date: 2025-01-07CHONGQING WULONG DISTRICT TRAFFIC ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581664.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During service, asphalt materials are susceptible to aging by factors such as temperature, oxygen, ultraviolet rays and water, resulting in degradation of performance, resulting in cracks, pits, looseness and other diseases on the asphalt pavement, shortening their service life.

Method used

Using high-strength asphalt composite materials, nanocellulose and zinc oxide are used in the preparation process of reinforced fillers and fibers by adding waste rubber powder, reinforced fillers and modified polyimide fibers, modified zinc oxide and nanocellulose. The synergistic effect with biphenyl structure improves the aging resistance and waterproof performance of asphalt composite materials.

Benefits of technology

It significantly improves the aging resistance and durability of asphalt composite materials, enhances the resistance to rut, deformation and cracking, delays the aging process, maintains good adhesion and stability, reduces maintenance costs, and extends the asphalt The service life of the road surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005123277880000111
    Figure BDA0005123277880000111
Patent Text Reader

Abstract

The invention relates to the technical field of asphalt materials, and discloses a high-strength asphalt composite material and a preparation method thereof. According to the high-strength asphalt composite material prepared by the invention, the asphalt is used as a base material, and the waste rubber powder is added, so that the stability of the asphalt composite material is improved, and the production cost is reduced; due to the addition of the reinforcing filler, the aging resistance and durability of the matrix are improved; due to the addition of the modified polyimide fiber, the excellent mechanical property and waterproof property of the modified polyimide fiber can be exerted, and a reinforcing effect on a matrix is achieved. Therefore, the asphalt composite material disclosed by the invention has a good application prospect when being applied to the fields of road construction and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of asphalt materials, and in particular to a high-strength asphalt composite material and a preparation method thereof. Background Art

[0002] With the continuous improvement of my country's transportation infrastructure network, highway construction has developed rapidly. Compared with ordinary cement pavement, asphalt pavement is increasingly widely used in highway construction due to its excellent road performance, smooth and seamless, comfortable driving, low noise, easy maintenance and other advantages. However, asphalt, as an organic material, is easily aged during service due to environmental factors such as temperature, oxygen, ultraviolet rays and water, resulting in deterioration of asphalt performance, such as significant decreases in low-temperature cracking resistance and high-temperature deformation resistance, which causes asphalt pavement to be prone to cracks, potholes, rutting, looseness, surface damage and other diseases, which not only endangers the smooth flow of transportation and driving safety, but also greatly shortens the service life of asphalt pavement.

[0003] Asphalt aging can be divided into thermal oxidative aging and photo-oxidative aging. Thermal oxidative aging will cause asphalt to become hard and brittle, and its physical properties will change significantly, making the asphalt pavement prone to cracks, potholes, surface damage and other diseases. After UV aging, it will become hard and brittle, and the softening point and viscosity will increase rapidly, while the penetration and elongation will drop sharply. In addition, the adhesion between asphalt and aggregate will decrease after UV aging, making the asphalt pavement very prone to cracks and potholes. Therefore, improving the aging resistance of asphalt, reducing the maintenance cost of asphalt pavement, and extending the service life of asphalt pavement are of great practical significance for promoting the sustainable development of highway construction. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a high-strength asphalt composite material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A high-strength asphalt composite material, comprising the following raw materials in parts by weight: 100 parts of asphalt, 8-15 parts of waste rubber powder, 5-10 parts of reinforcing filler, 0.5-2 parts of modified polyimide fiber, and 0.3-0.6 parts of stabilizer;

[0007] The reinforcing filler is prepared by the following steps:

[0008] Step A1, disperse and stir the nanocellulose in dichloromethane, then add 3-chloropropylamine hydrochloride and sodium hydroxide, stir and react for 15-20 hours, centrifuge and purify to obtain functionalized cellulose;

[0009] Step A2, 4,4'-dihydroxybiphenyl and glyoxylic acid are mixed and stirred evenly, and the mixture is heated to 90-110°C, stirred for 20-40 minutes, and then nitrogen is introduced, and cyclohexane and p-toluenesulfonic acid are added at the same time, and the mixture is heated to 135-145°C for reaction for 1 hour, and then the introduction of nitrogen is stopped, and the reaction is continued under vacuum conditions for 1.5-2.5 hours, and purified to obtain a cross-linking monomer;

[0010] Step A3, adding the functionalized cellulose to a 3-5wt% cross-linking monomer aqueous solution and stirring evenly, heating to 40-50°C and stirring to react for 1-2h, centrifuging, washing, and then adding to a modified zinc oxide solution, maintaining the temperature and continuing to react for 3-5h, centrifuging, washing, and then adding a 10-15mg / mL sodium cyanoborohydride solution to react for 2-3h, centrifuging, washing, and drying to obtain a reinforced filler;

[0011] Further, in step A1, the usage ratio of nanocellulose, dichloromethane, 3-chloropropylamine hydrochloride and sodium hydroxide is 1-3 g: 100 mL: 2-4 g: 1-3 g;

[0012] Further, in step A2, the usage ratio of 4,4'-dihydroxybiphenyl, glyoxylic acid, cyclohexane and p-toluenesulfonic acid is 0.1-0.2 mol: 0.2-0.4 mol: 10-20 mL: 0.4-0.5 g;

[0013] Further, in step A3, the amount ratio of the functionalized cellulose, the cross-linking monomer aqueous solution, the modified zinc oxide solution and the sodium cyanoborohydride solution is 1-3 g: 10-20 mL: 10 mL: 5 mL;

[0014] Furthermore, the modified zinc oxide solution in step A3 is prepared by the following steps: dispersing 0.1-1 g of γ-aminopropyltriethoxysilane in 50 mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjusting the pH to 8-9, adding 0.5-1.5 g of zinc oxide nanosheets and ultrasonicating for 10-20 min, stirring and reacting for 2-3 h, centrifuging, washing, and re-dispersing in 10 mL of deionized water to obtain a modified zinc oxide solution.

[0015] The modified polyimide fiber is prepared by the following steps:

[0016] Step B1, 3,5-dinitrobenzoic acid and 1H,1H-perfluoroheptylamine are placed in a flask, and heated to 110-130° C. under nitrogen conditions, condensed and refluxed for 8-10 hours, and then heated to 150° C. to continue the reaction for 2-3 hours to obtain a nitro compound;

[0017] Step B2, heating the nitro compound, palladium / carbon catalyst and anhydrous ethanol in a flask to 75-85° C., then adding hydrazine hydrate dropwise and reflux for 5-8 hours, then adding tetrahydrofuran and reflux for 25-35 minutes, filtering, concentrating and recrystallizing to obtain a diamine monomer;

[0018] Step B3, under nitrogen conditions, add diamine monomer, p-phenylenediamine and dimethylacetamide into a reactor and stir for 15-25 minutes, add pyromellitic anhydride three times, react at 0°C for 2 hours, and then react at room temperature for 6-10 hours, evaporate under reduced pressure, add DMF and 1-methyl-2-pyrrolidone and stir for 20 minutes, reduce pressure and filter to obtain a spinning solution, wet-spin the spinning solution through a spinneret, wash the obtained fiber with water, and then place it in a tubular furnace for hot drawing, collect the fiber and cut it into a length of 2-4 mm to obtain a modified polyimide fiber;

[0019] Further, in step B1, the molar ratio of 3,5-dinitrobenzoic acid to 1H,1H-perfluoroheptylamine is 1:1;

[0020] Further, in step B2, the usage ratio of the nitro compound, palladium / carbon catalyst, anhydrous ethanol, hydrazine hydrate and tetrahydrofuran is 0.01-0.05 mol: 1-3 g: 120 mL: 25-35 mL: 100 mL;

[0021] Further, in step B3, the usage ratio of diamine monomer, p-phenylenediamine, dimethylacetamide, pyromellitic dianhydride, DMF and 1-methyl-2-pyrrolidone is 1-3 g: 5-9 g: 100 mL: 4.5-5.5 g: 90 mL: 30 mL;

[0022] Furthermore, during the hot stretching process in step B3, the first stretching temperature is 180-200°C, the stretching ratio is 3, the second stretching temperature is 240-280°C, the stretching ratio is 3, and the third stretching temperature is 320-360°C, the stretching ratio is 1.

[0023] A method for preparing a high-strength asphalt composite material comprises the following steps:

[0024] Weigh the raw materials by weight, add asphalt, waste rubber powder, reinforcing filler and stabilizer (sulfur) into a stirrer, stir for 30-50 minutes at 190-220°C and 200-250rpm / min, then add modified polyimide fiber and stir at 260-300rpm / min for 50-80 minutes to obtain a high-strength asphalt composite material.

[0025] Beneficial effects of the present invention:

[0026] The high-strength asphalt composite material prepared by the present invention is based on asphalt. The addition of waste rubber powder improves the stability of the asphalt composite material and reduces the production cost. The addition of reinforcing fillers improves the aging resistance and durability of the matrix. The addition of modified polyimide fibers can exert their own excellent mechanical properties and waterproof properties to reinforce the matrix. Therefore, the asphalt composite material of the present invention has a good application prospect in the fields of road construction and the like.

[0027] In the reinforcing filler, the hydroxyl groups in the nanocellulose and the chlorine atoms in 3-chloropropylamine hydrochloride are firstly reacted to obtain functionalized cellulose; then the hydroxyl groups in 4,4'-dihydroxybiphenyl and the carboxyl groups in glyoxylic acid are reacted to obtain a crosslinking monomer; and then the functionalized cellulose and modified zinc oxide are compounded with the crosslinking monomer to obtain the reinforcing filler. Through the synergistic effect of nanocellulose, zinc oxide nanosheets and biphenyl structure, the reinforcing filler can be evenly dispersed in the asphalt, thereby improving the comprehensive performance of the asphalt composite material; among them, nanocellulose is evenly dispersed in the matrix, and can use its own excellent mechanical properties to significantly improve the road performance of asphalt, including anti-rutting, anti-deformation and anti-cracking properties; nanocellulose can also synergize with zinc oxide nanosheets, using the layered structure to effectively block oxygen and heat from entering the asphalt, inhibit the oxidation reaction of the asphalt, and at the same time prevent the volatilization of light components in the asphalt, reduce the change in asphalt quality before and after aging, and improve the durability of the matrix; in addition, zinc oxide nanosheets in the matrix can also use their excellent ultraviolet light absorption ability to increase the matrix's absorption intensity of ultraviolet light, thereby delaying the aging process of the matrix. At the same time, the biphenyl structure also has a certain ultraviolet light absorption effect, which further improves the durability of the matrix.

[0028] In the modified polyimide fiber, 3,5-dinitrobenzoic acid and 1H,1H-perfluoroheptyl are first used as raw materials to synthesize a nitro compound, and then hydrazine hydrate is used as a reducing agent to reduce the nitro compound to a diamine monomer, and finally the diamine monomer and p-phenylenediamine are used as diamine, and pyromellitic acid dianhydride is used as dianhydride to synthesize the modified polyimide fiber; the introduction of the modified polyimide fiber can significantly improve the performance of the asphalt composite material, because after the fiber is filled with asphalt, it can have a reinforcing effect on the asphalt, and can maximize its strengthening, reinforcement and toughening effects, so that the modified asphalt mixture has improved various road performances; the fluorine element introduced into the modified polyimide fiber can also significantly improve the waterproof performance of the asphalt, so that it can still maintain good adhesion and stability in a humid environment, and reduce the influence of moisture on the performance of the asphalt. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] The reinforcing filler is prepared by the following steps:

[0032] Step A1, disperse 1g of nanocellulose in 100mL of dichloromethane and stir evenly, then add 2g of 3-chloropropylamine hydrochloride and 1g of sodium hydroxide, stir and react for 15h, centrifuge and purify to obtain functionalized cellulose;

[0033] Step A2, 0.1 mol 4,4'-dihydroxybiphenyl and 0.2 mol glyoxylic acid were mixed and stirred evenly, and the mixture was heated to 90°C and stirred for 20 min, and then nitrogen was introduced, and 10 mL cyclohexane and 0.4 g p-toluenesulfonic acid were added at the same time, and the mixture was heated to 135°C and reacted for 1 h, and then the nitrogen was stopped, and the reaction was continued under vacuum conditions for 1.5 h, and purified to obtain a cross-linking monomer;

[0034] Step A3, add 1g of functionalized cellulose to 10mL, 5wt% aqueous solution of cross-linked monomer and stir evenly, heat to 40℃ and stir to react for 1h, centrifuge, wash, add to 10mL of modified zinc oxide solution, maintain the temperature and continue to react for 3h, centrifuge, wash, add 5mL, 10mg / mL sodium cyanoborohydride solution and react for 2h, centrifuge, wash, and dry to obtain reinforced filler. The modified zinc oxide solution is prepared by the following steps: 0.1g of γ-aminopropyltriethoxysilane is dispersed in 50mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjust the pH to 8, add 0.5g of zinc oxide nanosheets and ultrasonicate for 10min, stir to react for 2h, centrifuge, wash, and redisperse in 10mL of deionized water to obtain modified zinc oxide solution.

[0035] The modified polyimide fiber is prepared by the following steps:

[0036] Step B1, 0.1 mol 3,5-dinitrobenzoic acid and 0.1 mol 1H,1H-perfluoroheptylamine were placed in a flask, and heated to 110° C. under nitrogen conditions, condensed and refluxed for 8 h, and then heated to 150° C. to continue the reaction for 2 h to obtain a nitro compound;

[0037] Step B2, 0.01 mol of nitro compound, 1 g of palladium / carbon catalyst and 120 mL of anhydrous ethanol were heated to 75° C. in a flask, and then 25 mL of hydrazine hydrate was added dropwise and refluxed for 5 h, and then 100 mL of tetrahydrofuran was added and refluxed for 25 min, filtered, concentrated, and recrystallized to obtain a diamine monomer;

[0038] Step B3, under nitrogen conditions, 1g of diamine monomer, 9g of p-phenylenediamine and 100mL of dimethylacetamide were added to the reactor and stirred for 15min, 4.5g of pyromellitic anhydride was added three times, reacted at 0°C for 2h, and then reacted at room temperature for 6h, vacuum rotary evaporation, 90mL of DMF and 30mL of 1-methyl-2-pyrrolidone were added and stirred for 20min, and then the spinning solution was decompressed and filtered to obtain a spinning solution, and the spinning solution was wet-spun through a spinneret, and the obtained fiber was washed with water and then placed in a tubular furnace for hot drawing, and the fiber was collected and cut into a length of 2mm to obtain a modified polyimide fiber. During the hot drawing process, the first drawing temperature was 180°C, the drawing ratio was 3, the second drawing temperature was 240°C, the drawing ratio was 3, and the third drawing temperature was 320°C, and the drawing ratio was 1.

[0039] Example 2

[0040] The reinforcing filler is prepared by the following steps:

[0041] Step A1, disperse 2 g of nanocellulose in 100 mL of dichloromethane and stir evenly, then add 3 g of 3-chloropropylamine hydrochloride and 2 g of sodium hydroxide, stir and react for 17 h, centrifuge and purify to obtain functionalized cellulose;

[0042] Step A2, 0.15 mol of 4,4'-dihydroxybiphenyl and 0.3 mol of glyoxylic acid were mixed and stirred evenly, and the mixture was heated to 100°C and stirred for 30 min, and then nitrogen was introduced, and 15 mL of cyclohexane and 0.45 g of p-toluenesulfonic acid were added at the same time, and the mixture was heated to 140°C and reacted for 1 h, and then the introduction of nitrogen was stopped, and the reaction was continued under vacuum conditions for 2 h, and purified to obtain a cross-linking monomer;

[0043] Step A3, add 2g of functionalized cellulose to 15mL, 4wt% aqueous solution of cross-linked monomer and stir evenly, heat to 45℃ and stir to react for 1.5h, centrifuge, wash, add to 10mL of modified zinc oxide solution, maintain the temperature and continue to react for 4h, centrifuge, wash, add 5mL, 12mg / mL sodium cyanoborohydride solution and react for 2.5h, centrifuge, wash, and dry to obtain reinforced filler. The modified zinc oxide solution is prepared by the following steps: 0.5g of γ-aminopropyltriethoxysilane is dispersed in 50mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjust the pH to 8.5, add 1g of zinc oxide nanosheets and ultrasonicate for 15min, stir and react for 2.5h, centrifuge, wash, and redisperse in 10mL of deionized water to obtain modified zinc oxide solution.

[0044] The modified polyimide fiber is prepared by the following steps:

[0045] Step B1, 0.1 mol 3,5-dinitrobenzoic acid and 0.1 mol 1H,1H-perfluoroheptylamine were placed in a flask, and heated to 120° C. under nitrogen conditions, condensed and refluxed for 9 hours, and then heated to 150° C. to continue the reaction for 2.5 hours to obtain a nitro compound;

[0046] Step B2, 0.03 mol of nitro compound, 2 g of palladium / carbon catalyst and 120 mL of anhydrous ethanol were heated to 80° C. in a flask, and then 30 mL of hydrazine hydrate was added dropwise and refluxed for 6.5 h, and then 100 mL of tetrahydrofuran was added and refluxed for 30 min, filtered, concentrated, and recrystallized to obtain a diamine monomer;

[0047] Step B3, under nitrogen conditions, 2g of diamine monomer, 8g of p-phenylenediamine and 100mL of dimethylacetamide were added to the reactor and stirred for 20min, 5g of pyromellitic anhydride was added three times, reacted at 0°C for 2h, and then reacted at room temperature for 8h, vacuum rotary evaporation, 90mL of DMF and 30mL of 1-methyl-2-pyrrolidone were added and stirred for 20min, and then the spinning solution was obtained by decompression and filtration. The spinning solution was wet-spun through a spinneret, the obtained fiber was washed with water, and then placed in a tubular furnace for hot drawing, and the fiber was collected and cut into a length of 3mm to obtain a modified polyimide fiber. During the hot drawing process, the first drawing temperature was 190°C, the drawing ratio was 3, the second drawing temperature was 260°C, the drawing ratio was 3, and the third drawing temperature was 340°C, and the drawing ratio was 1.

[0048] Example 3

[0049] The reinforcing filler is prepared by the following steps:

[0050] Step A1, disperse 3 g of nanocellulose in 100 mL of dichloromethane and stir evenly, then add 4 g of 3-chloropropylamine hydrochloride and 3 g of sodium hydroxide, stir and react for 20 hours, centrifuge and purify to obtain functionalized cellulose;

[0051] Step A2, 0.2 mol 4,4'-dihydroxybiphenyl and 0.4 mol glyoxylic acid were mixed and stirred evenly, and the mixture was heated to 110°C and stirred for 40 min, and then nitrogen was introduced, and 20 mL cyclohexane and 0.5 g p-toluenesulfonic acid were added at the same time, and the mixture was heated to 145°C and reacted for 1 h, and then the nitrogen was stopped, and the reaction was continued under vacuum conditions for 2.5 h, and purified to obtain a cross-linking monomer;

[0052] Step A3, add 3g of functionalized cellulose to 20mL, 3wt% aqueous solution of cross-linked monomer and stir evenly, heat to 50℃ and stir to react for 2h, centrifuge, wash, add to 10mL of modified zinc oxide solution, maintain the temperature and continue to react for 5h, centrifuge, wash, add 5mL, 15mg / mL sodium cyanoborohydride solution and react for 3h, centrifuge, wash, and dry to obtain reinforced filler. The modified zinc oxide solution is prepared by the following steps: disperse 1g of γ-aminopropyltriethoxysilane in 50mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjust the pH to 9, add 1.5g of zinc oxide nanosheets and ultrasonicate for 20min, stir to react for 3h, centrifuge, wash, and redisperse in 10mL of deionized water to obtain modified zinc oxide solution.

[0053] The modified polyimide fiber is prepared by the following steps:

[0054] Step B1, 0.1 mol 3,5-dinitrobenzoic acid and 0.1 mol 1H,1H-perfluoroheptylamine were placed in a flask, and heated to 130° C. under nitrogen conditions, condensed and refluxed for 10 h, and then heated to 150° C. and continued to react for 3 h to obtain a nitro compound;

[0055] Step B2, 0.05 mol of nitro compound, 3 g of palladium / carbon catalyst and 120 mL of anhydrous ethanol were heated to 85° C. in a flask, and then 35 mL of hydrazine hydrate was added dropwise and refluxed for 8 h, and then 100 mL of tetrahydrofuran was added and refluxed for 35 min, filtered, concentrated, and recrystallized to obtain a diamine monomer;

[0056] Step B3, under nitrogen conditions, 3g of diamine monomer, 9g of p-phenylenediamine and 100mL of dimethylacetamide were added to the reactor and stirred for 25min, 5.5g of pyromellitic anhydride was added three times, reacted at 0°C for 2h, and then reacted at room temperature for 10h, vacuum rotary evaporation, 90mL of DMF and 30mL of 1-methyl-2-pyrrolidone were added and stirred for 20min, and then the spinning solution was reduced pressure and filtered to obtain a spinning solution, and the spinning solution was wet-spun through a spinneret, and the obtained fiber was washed with water and then placed in a tubular furnace for hot drawing, and the fiber was collected and cut into a length of 4mm to obtain a modified polyimide fiber. During the hot drawing process, the first stretching temperature was 200°C and the stretching ratio was 3, the second stretching temperature was 280°C, the stretching ratio was 3, and the third stretching temperature was 360°C, and the stretching ratio was 1.

[0057] Example 4

[0058] A method for preparing a high-strength asphalt composite material comprises the following steps:

[0059] 100 parts of asphalt, 8 parts of waste rubber powder, 5 parts of reinforcing filler prepared in Example 1, 0.5 parts of modified polyimide fiber prepared in Example 1, and 0.3 parts of stabilizer (sulfur);

[0060] Weigh the raw materials by weight, add asphalt, waste rubber powder, reinforcing filler prepared in Example 1, and stabilizer (sulfur) into a stirrer, stir for 30 minutes at 190°C and 200 rpm / min, then add the modified polyimide fiber prepared in Example 1, stir at 260 rpm / min for 50 minutes to obtain a high-strength asphalt composite material.

[0061] Example 5

[0062] A method for preparing a high-strength asphalt composite material comprises the following steps:

[0063] 100 parts of asphalt, 12 parts of waste rubber powder, 8 parts of reinforcing filler prepared in Example 2, 1 part of modified polyimide fiber prepared in Example, and 0.5 parts of stabilizer (sulfur);

[0064] Weigh the raw materials by weight, add asphalt, waste rubber powder, reinforcing filler prepared in Example 2, and stabilizer (sulfur) into a stirrer, stir for 40 minutes at 210°C and 230 rpm / min, then add the modified polyimide fiber prepared in Example 2, stir for 60 minutes at 280 rpm / min to obtain a high-strength asphalt composite material.

[0065] Example 6

[0066] A method for preparing a high-strength asphalt composite material comprises the following steps:

[0067] 100 parts of asphalt, 15 parts of waste rubber powder, 10 parts of reinforcing filler prepared in Example 3, 2 parts of modified polyimide fiber prepared in Example 3, and 0.6 parts of stabilizer (sulfur);

[0068] The raw materials were weighed by weight, and asphalt, waste rubber powder, reinforcing filler prepared in Example 3 and stabilizer (sulfur) were added into a stirrer, and stirred at 220°C and 250 rpm / min for 50 min. Then, the modified polyimide fiber prepared in Example 3 was added, and stirred at 300 rpm / min for 80 min to obtain a high-strength asphalt composite material.

[0069] Comparative Example 1

[0070] This comparative example is an asphalt composite material, which is different from Example 6 in that calcium carbonate is used instead of the reinforcing filler prepared in Example 3, and the rest is the same.

[0071] Comparative Example 2

[0072] This comparative example is an asphalt composite material, which is different from Example 6 in that polyimide fiber is used instead of the modified polyimide fiber prepared in Example 3, and the rest is the same.

[0073] The asphalt composite materials prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:

[0074] Ductility test: GB / T0605-1993 is used as the experimental standard to test the ductility of the sample at 5°C;

[0075] Thermal oxidative aging performance test: Using a thin film oven test, place the test sample at 163°C for 5 hours, and then test the ductility at 5°C;

[0076] UV aging performance test: The samples after thermal oxygen aging are placed in a UV aging oven. The distance between the asphalt sample and the high-pressure mercury lamp is adjusted to control the intensity of UV light irradiated to the upper surface of the asphalt to 2000μW / cm 2 , the asphalt UV aging test environment was set to 60±3℃, the asphalt aging time was 7d, and the ductility was tested at 5℃;

[0077] Elastic recovery test: GB / T 0661-1998 is used as the experimental standard. At 25°C, stretch the sample to 10cm at a stretching speed of 5°C / min, cut the sample from the middle, keep the water temperature for 1h, and measure the percentage of recoverable deformation of the sample;

[0078] Segregation test: GB / T 0661-2000 is used as the experimental standard. The sample is placed in a 163℃ oven for 48 hours. The difference in softening point is measured by the ring and ball method at the upper and lower 1 / 3 ends of the sample.

[0079] Waterproof performance test: Use a contact angle meter to measure the contact angle of water droplets on the sample surface;

[0080] The test results are shown in Table 1:

[0081] Table 1

[0082]

[0083] As can be seen from Table 1, after aging performance, elastic recovery performance, segregation performance, waterproof performance and ductility performance tests, the asphalt composite material prepared by the present invention has excellent aging resistance, mechanical properties, storage stability and waterproof performance; therefore, it has a good application prospect in the fields of road construction and so on.

[0084] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength asphalt composite material, characterized in that: The raw materials include the following parts by weight: 100 parts of asphalt, 8-15 parts of waste rubber powder, 5-10 parts of reinforcing filler, 0.5-2 parts of modified polyimide fiber, and 0.3-0.6 parts of stabilizer; The reinforcing filler is prepared by the following steps: Step A1, disperse and stir the nanocellulose in dichloromethane, then add 3-chloropropylamine hydrochloride and sodium hydroxide, stir and react for 15-20 hours, centrifuge and purify to obtain functionalized cellulose; Step A2, 4,4'-dihydroxybiphenyl and glyoxylic acid are mixed and stirred evenly, and the mixture is heated to 90-110°C, stirred for 20-40 minutes, and then nitrogen is introduced, and cyclohexane and p-toluenesulfonic acid are added at the same time, and the mixture is heated to 135-145°C for reaction for 1 hour, and then the introduction of nitrogen is stopped, and the reaction is continued under vacuum conditions for 1.5-2.5 hours, and purified to obtain a cross-linking monomer; Step A3, adding the functionalized cellulose to a 3-5wt% cross-linking monomer aqueous solution and stirring evenly, heating to 40-50°C and stirring to react for 1-2h, centrifuging and washing, then adding to the modified zinc oxide solution, maintaining the temperature and continuing to react for 3-5h, centrifuging and washing, then adding 10-15mg / mL sodium cyanoborohydride solution to react for 2-3h, centrifuging, washing, and drying to obtain a reinforced filler.

2. A high-strength asphalt composite material according to claim 1, characterized in that: In step A1, the usage ratio of nanocellulose, dichloromethane, 3-chloropropylamine hydrochloride and sodium hydroxide is 1-3 g:100 mL:2-4 g:1-3 g.

3. The high-strength asphalt composite material according to claim 1, characterized in that: In step A2, the usage ratio of 4,4'-dihydroxybiphenyl, glyoxylic acid, cyclohexane and p-toluenesulfonic acid is 0.1-0.2 mol: 0.2-0.4 mol: 10-20 mL: 0.4-0.5 g.

4. The high-strength asphalt composite material according to claim 1, characterized in that: In step A3, the dosage ratio of the functionalized cellulose, the cross-linking monomer aqueous solution, the modified zinc oxide solution and the sodium cyanoborohydride solution is 1-3 g: 10-20 mL: 10 mL: 5 mL.

5. The high-strength asphalt composite material according to claim 1, characterized in that: The modified zinc oxide solution in step A3 is prepared by the following steps: 0.1-1 g of γ-aminopropyltriethoxysilane is dispersed in 50 mL of ethanol solution, the pH is adjusted to 8-9, 0.5-1.5 g of zinc oxide nanosheets are added, ultrasonicated for 10-20 min, stirred for reaction for 2-3 h, centrifuged, washed, and redispersed in 10 mL of deionized water to obtain a modified zinc oxide solution.

6. The high-strength asphalt composite material according to claim 1, characterized in that: The modified polyimide fiber is prepared by the following steps: Step B1, 3,5-dinitrobenzoic acid and 1H,1H-perfluoroheptylamine are placed in a flask, and heated to 110-130° C. under nitrogen conditions, condensed and refluxed for 8-10 hours, and then heated to 150° C. to continue the reaction for 2-3 hours to obtain a nitro compound; Step B2, heating the nitro compound, palladium / carbon catalyst and anhydrous ethanol in a flask to 75-85° C., then adding hydrazine hydrate dropwise and reflux for 5-8 hours, then adding tetrahydrofuran and reflux for 25-35 minutes, filtering, concentrating and recrystallizing to obtain a diamine monomer; Step B3, under nitrogen conditions, add diamine monomer, p-phenylenediamine and dimethylacetamide into a reactor and stir for 15-25 minutes, add pyromellitic anhydride three times, react at 0°C for 2 hours, and then react at room temperature for 6-10 hours, evaporate under reduced pressure, add DMF and 1-methyl-2-pyrrolidone and stir for 20 minutes, reduce pressure and filter to obtain a spinning solution, wet-spin the spinning solution through a spinneret, wash the obtained fiber with water, and then place it in a tubular furnace for hot drawing, collect and cut the silk into a length of 2-4 mm to obtain a modified polyimide fiber.

7. The high-strength asphalt composite material according to claim 6, characterized in that: The molar ratio of 3,5-dinitrobenzoic acid to 1H,1H-perfluoroheptylamine in step B1 is 1:

1.

8. The high-strength asphalt composite material according to claim 6, characterized in that: In step B2, the usage ratio of the nitro compound, palladium / carbon catalyst, anhydrous ethanol, hydrazine hydrate and tetrahydrofuran is 0.01-0.05 mol: 1-3 g: 120 mL: 25-35 mL: 100 mL.

9. The high-strength asphalt composite material according to claim 6, characterized in that: In step B3, the amount ratio of diamine monomer, p-phenylenediamine, dimethylacetamide, pyromellitic anhydride, DMF and 1-methyl-2-pyrrolidone is 1-3g:5-9g:100mL:4.5-5.5g:90mL:30mL. During the hot stretching process, the first stretching temperature is 180-200°C, the stretching ratio is 3, the second stretching temperature is 240-280°C, the stretching ratio is 3, and the third stretching temperature is 320-360°C, and the stretching ratio is 1.

10. A method for preparing the high-strength asphalt composite material according to any one of claims 1 to 9, characterized in that: Follow these steps: Weigh the raw materials by weight, add asphalt, waste rubber powder, reinforcing filler and stabilizer into a stirrer, stir for 30-50 minutes at 190-220°C and 200-250rpm / min, then add modified polyimide fiber and stir at 260-300rpm / min for 50-80 minutes to obtain a high-strength asphalt composite material.